Fenomena Kecemasan Wanita Dalam Menghadapi Masa Klimakterium - Yuni Fitriana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Women climacterium will occur during certain changes that can cause disturbances in mild to severe. Most women climacterium not know that this change was a process of natural menopause. They were worried and confused about the symptoms that accompany therefore face the need to prepare themselves with sufficient knowledge about climacterium.Objective: The purpose of this study was to determine the phenomenon of anxiety in the face of the climacterium woman .Method: The method in this research is qualitative by using a phenomenological approach. This study used the research subjects were four informants were all the climactrium mothers who live in Candi subdistrik Semarang. Data was collected by indept interview.Results: showed that all subjects in general have to understand what was meant the climacterium and menopause. In the three informants experiencing anxiety about the advent of this climacterium which was marked by several symptoms such as dizziness, insomnia, burning sensation, fear, and so forth. At the first subject the matter was not felt, and this was reasonable because the first subject has passed through menopause.Conclusion: The research subjects generally had their own ways in dealing with anxiety. Ways of coping were either done by the subject can finally solve the various problems well too.Key words: Anxiety, Period of climacterium